Tuning Electron Transport Direction through the Deposition Sequence of MoS2 and WS2 on Fluorine‐Doped Tin Oxide for Improved Electrocatalytic Reduction Efficiency. Issue 10 (20th May 2019) - Liu, Yajuan; Yin, Jie; Zhou, Yuqing; Sun, Luo; Yue, Wenjin; Sun, Yueming; Wang, Yuqiao
Abstract: MoS2 −WS2 films on fluorine‐doped tin oxide (FTO) can be vulcanized through chemical vapor deposition by using MoO3 and WO3 as precursors prepared by pulsed laser deposition. The electron transport direction can be tuned by the deposition sequence of metal sulfides on FTO, owing to the differences in the conduction bands (CBs, MoS2 −4.38 vs. WS2 −4.13 eV), defined as the energy level impedance to adjust the electron transport rate. It means that the electron transport rate from FTO to the MoS2 surface of FTO/WS2 /MoS2 might be higher than the rate from FTO to the WS2 surface of FTO/MoS2 /WS2 . The assumption was verified by the electrocatalytic reduction of I3 − to I − using the above films as a counter electrode in a dye‐sensitized solar cell. The short‐circuit photocurrent density of FTO/WS2 /MoS2 achieved 14.16 mA cm −2, which is superior to FTO/MoS2 /WS2 (11.72 mA cm −2 ), indicating that the catalytic activity of FTO/WS2 /MoS2 was higher than that of FTO/MoS2 /WS2 . The electron transport direction can be successfully regulated by tuning the deposition order. Abstract : Don′t be impeded : The concept of "energy level impedance" is proposed with reference to the energy level and the impedance required to tune the electron transport direction through the deposition sequence of bilayered films.